2015
DOI: 10.1007/s12519-015-0072-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc supplementation on infants with severe pneumonia

Abstract: Zinc deficiency is common in infants with severe pneumonia. Normalization of zinc levels with zinc supplementation did not improve clinical outcomes of infants with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 11 publications
2
39
0
3
Order By: Relevance
“…Despite the earlier observed reduction of treatment failure risk (94) and case fatality [RR=0.67 (95% cI: 0.24-0.85)] (95) in children with severe pneumonia, a more recent study demonstrated that Zn supplementation in 2-24 months old children with radiologically verified pneumonia did not result in significant improvement of risk reduction of treatment failure (96). Moreover, Zn supplementation in Zn-deficient children with pneumonia until achievement of normal serum Zn levels did not improve clinical appearance of the disease (97).…”
Section: Pediatric Respiratory Infectionsmentioning
confidence: 88%
“…Despite the earlier observed reduction of treatment failure risk (94) and case fatality [RR=0.67 (95% cI: 0.24-0.85)] (95) in children with severe pneumonia, a more recent study demonstrated that Zn supplementation in 2-24 months old children with radiologically verified pneumonia did not result in significant improvement of risk reduction of treatment failure (96). Moreover, Zn supplementation in Zn-deficient children with pneumonia until achievement of normal serum Zn levels did not improve clinical appearance of the disease (97).…”
Section: Pediatric Respiratory Infectionsmentioning
confidence: 88%
“…Considering the known effects of zinc in regulating the immune system, trials have been conducted to investigate the efficacy of zinc in treating respiratory illnesses ( Table 8 ) [ 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ].…”
Section: Zincmentioning
confidence: 99%
“…In a 2018 study, serum zinc levels were found to be significantly lower among pneumonia pediatric patients admitted to PICU compared with patients admitted to other wards; there was a statistically significant decrease in zinc level in critically ill children complicated by sepsis, mechanically ventilated and fatal cases [ 252 ]. Some studies reported similar duration of hospital stay, time to symptoms resolution, and risk of treatment failure in the intervention and in the control group [ 254 , 255 , 256 , 258 , 259 , 262 , 264 , 265 ], while others described partially positive results. Basnet and colleagues [ 260 ] found that zinc recepients recovered slightly faster than controls, although the difference was not statistically significant; Sempertegui et al [ 263 ] evidenced that a higher basal zinc concentration was associated with faster resolution of chest indrawing, although there was no difference in time needed to fully recover nor in the risk of treatment failure; Mahalanbis et al found a reduced duration of ALRI symptoms in boys, but not in girls [ 253 ].…”
Section: Zincmentioning
confidence: 99%
“…[ 17 ] In children with pneumonia, a common respiratory infectious disease, zinc deficiency is highly prevalent (76.0%), but zinc supplementation seemed to not affect clinical outcomes. [ 18 ] In dengue disease, the role of zinc deficiency in the pathogenesis is still controversial. Yuliana et al .…”
Section: Discussionmentioning
confidence: 99%